The age of violence: the crisis of political action and the end of utopia - Bertho, Alain (Verso, 2018)
French divides -- The coming chaos -- The people, nowhere to be found? -- Youth on the front line -- The truth is out there, and god is online -- "What is now left to us" -- In praise of radicalism